Inappropriate expression of blood group antigens on biliary and colonic epithelia in primary sclerosing cholangitis. Issue 7 (July 1993) - Bloom, S; Heryet, A; Fleming, K; Chapman, R W
Abstract : The distribution of carbohydrate antigens of the ABO, Lewis, and Kell systems was examined in biliary and colonic epithelial of 11 patients with primary sclerosing cholangitis (PSC) using a panel of 11 monoclonal antibodies. Controls consisted of 27 liver biopsy specimens (11 normal, six alcoholic liver disease, five extrahepatic obstruction, and five primary biliary cirrhosis) and 24 colonic biopsy specimens (six normal, four Crohn's disease, and 14 ulcerative colitis). There was inappropriate staining with anti-A (four of six, 66%) and anti-B (nine of 11, 81%) in biliary epithelium of PSC patients compared with normal and disease controls. Expression of Lewis antigens was increased in patients with cholestatic liver disease. Ninety one per cent of PSC patients showed a similar pattern of inappropriate staining by anti-A and anti-B antibodies in colonic epithelium compared with 33% of normal and 42% of inflammatory bowel disease controls. There is inappropriate expression of A and B carbohydrate antigens in biliary and colonic epithelium in PSC. Whether these oncofetal antigens are implicated in the pathogenesis of this condition is discussed.